The association between state-level negative racial sentiment and maternal hypertension in the US from 2016 to 2021: An observational study using Twitter data - Laura B. Drew; Junaid Merchant; Marie E. Thoma; Heran Mane; Xiaohe Yue; Thu T. Nguyen (PLoS ONE, 2026)
Background Racial disparities in maternal hypertension (i.e., prepregnancy and gestational) due to experiences of racism may contribute to ongoing racial disparities in US birth outcomes, including low birth weight and preterm birth. Despite evidence linking racism and adverse birth outcomes, no studies have examined the plausible association between area-level negative racial sentiment and disparities in maternal hypertension. To address this gap, we used 2016–2021 US birth certificate data to examine the associations between state-level Twitter-derived negative sentiments toward racial/ethnic minorities and maternal hypertension. We further examined if these associations increased during periods of heightened racial discrimination. Methods We used 2016–2021 US natality data with geographic identifiers for pregnancy data for singleton births (n = 22,618,566) and a random sample of 1% of publicly available tweets from 2016–2021 (n = 56,400,097) using Twitter’s Academic Application Programming Interface. We calculated annual state-level negative racial sentiment by averaging sentiment scores of all posts referencing a racial category. These scores, divided into quartiles, included five sentiment measures: one toward all racially minoritized groups and four race-specific (Black, Asian, Latinx, and White). We merged data for each year and used log-binomial regression to estimate prevalence rate ratios (PRRs) for prepregnancy and gestational hypertension, adjusting for individual maternal characteristics and state-level demographics. We additionally stratified analyses into time periods before and during the COVID-19 pandemic and Black Lives Matter movement (2016–2019 and 2020–2021, respectively). Results In our sample, 2.2% of individuals had prepregnancy hypertension and 7.7% had gestational hypertension. From 2016−2021, the prevalence of both types of maternal hypertension increased for individuals across all racial and ethnic groups. Individuals in states with the highest quartile of negative racial minority sentiment had a 36% higher (95% CI: 1%−83%) prevalence of prepregnancy hypertension and a 20% higher (95% CI: 0%−45%) prevalence of gestational hypertension compared to those in the lowest quartile. In 2020 and 2021, the prevalence of prepregnancy hypertension among individuals in racially minoritized groups was 51% greater (95% CI:12%−103%) in the 4 th quartile compared to the 1 st quartile and showed a higher magnitude of association compared to 2016−2019. In 2020−2021, among Black individuals, those in the highest quartile of anti-Black sentiment had a 31% higher (95% CI: 2%−69%) prevalence of prepregnancy hypertension, and the 19% increase in prepregnancy hypertension among Asian individuals in the highest quartile of anti-Asian sentiment was borderline significant (95% CI: 0%−44%). Patterns for gestational hypertension were not consistent across time and when examining race-specific sentiment. Conclusion Higher levels of state-level negative racial sentiment are associated with increased prevalence of prepregnancy and gestational hypertension among racially minoritized groups, and the association with prepregnancy hypertension appears to strengthen during periods of heightened racial tension and discrimination. These findings highlight the role of area-level racism as a contributor to maternal health disparities.